Exploring competencies: a qualitative study of Chinese nurse managers. (24th March 2015) - Luo, Wen‐Yi; Shen, Nan‐Ping; Lou, Jian‐Hua; He, Ping‐Ping; Sun, Ji‐Wen
Abstract : Aim: To identify core competencies needed in the transition of nurse managers on the way to excellence. Background: There is growing recognition of the importance of nurse managers in hospitals. Most managers still learn through their failures and few studies have described the perceptions of nurse managers in China. It is vital to understand what competencies Chinese nurse managers should have in order to establish suitable training programmes and improve their management skills. Method: A phenomenological approach that included in‐depth interviews with 12 nurse managers in six Chinese hospitals was conducted. Results: The transition to management included four phases: the adaptive phase, the running‐in and stable phase, the stagnation phase and the maturation phase. Conclusion: In order to fulfil their clinical responsibilities, nurse managers need to develop multifaceted competencies, specifically in communication and stress management. Ideally, nurse managers should progress through the four phases mentioned above to achieve excellence. Implications: There is a requirement for utilising various methods for nurse managers in adapting new roles, improving communication and relieving stress.